Classroom practices of low-cost STEM education using scratch - KAZUNORI YAMAMORI (Journal of Advanced Research in Social Sciences and Humanities, 2019)
Aim: The purpose of this study is to demonstrate the potential of Scratch for STEM instruction. Drones and mobile robots can be navigated using Scratch. Mobile robots and inexpensive drones are also available. The author suggests a budget-friendly STEM education. Scratch is a great way to introduce kids to computer programming. The STEM disciplines can also be taught with Scratch. The research here suggests using Scratch as a low-cost tool for STEM education.Method: The current investigation employs a qualitative descriptive strategy. The Scratch app was developed and used with kids to achieve the results. Findings: The results demonstrate that STEM education through Scratch can be provided at a lower cost. Learning occurs in a group of 6 or 7 students when a teacher assigns a task in which robots must move forward while dodging obstacles built from LEGO bricks. Each student can focus on the assignment at hand with the help of a low-cost mobile robot, should the instructor choose. If the instructor decides to use Scratch exclusively, students can engage in activities requiring them to think critically about the problem.Implications/Novel Contribution: Creativity training is at the heart of STEM curricula. Many Japanese cities host annual robot competitions. A robot-building competition is a fun way to encourage original thought. As a result, more students would benefit from learning to code. Inexpensive mobile robots and drones that can be piloted with Scratch are becoming increasingly popular. Less expensive teaching materials are necessary if we force each student to engage with the issue.